George'a Berkeleya koncepcja świata i przyrody - Płachciak, Adam (George Berkeley's concept of the world and nature, 2006)
The purpose of the paper is to show the religious apology, being without any doubts the main motivation of G. Berkeley’s philosophical reflection. The Irish thinker made a challenge to create a modern and an opened formula of defending reviled theology being in a danger of contemporary philosophical trends. In his apology, he managed to overcome the basic problems arising from Cartesian philosophy. As a consequence of the attitude, Malebranche’s ontologism, Locke’s phenomenology and Cartesian nativism were questioned. In fact the biggest enemy of Berkeley’s philosophy was the contemporary concept of matter. He believed that receiving material substance as a base of existence might lead into the skepticism and atheism. Questioning the existence of matter bishop of Cloyne abolished traditional, dualistic metaphysics which divided substance between matter and spirit. According to Berkeley’s philosophy, the existence of things is only possible in the minds of spiritual things (beings). There was his famous Latin saying: esse est percipi aut percipere. The visual world in perceiving minds is the result of created action of God. The world is the Book of Nature written by the Author of Nature, empirically experienced things are the Works of Nature, the signs of Optical Language which is ordered by the Rules or the Laws of Nature. In contrast to deistic philosophy, which reduced any influence of God in the physical world, Berkeley presented the world as the visual theophany, as the divine discourse which gave man great opportunities to take part in God’s perceptions and his thoughts.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (5); 2006; nr 1115, s. 150-155